EVALUASI PROGRAM GEBYAR PENDIDIKAN MASYARAKAT - Alvan, Eri Nur; Aditya, Aditya; Herdiani, Sherli; Rahmawati, Dewi; Rofi'ah, Fidia Huwaida (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2023)
Abstract. The art of decorating nails that are applicable for daily activities is quite in demand by young people, the art of decorating nails or nail art also has uses to help women overcome problems such as wavy nails that break easily, or those who want to extend their nails. So the provision of this nail art training program is expected to help the public be literate about the business opportunities that we specifically target the art of nail decorating so that the participants get a moral boost and provide a more structured introduction to the stages of nail art or the hobbies they channel to become productive business fields. The research sample is a total population consisting of 39 Nail Art training participants. The tool used is a questionnaire based on the CIPP model evaluation indicators.